Studentu/šu korporāciju dokumentālās liecības par LU Karoga fonda neizveidošanos - Rubenis, Rūdolfs (LU Muzejs, 2022)
Raksts ir turpinājums LU Muzeja 2021. gada septembra Mēneša priekšmetam "Latvijas Universitātes vēsturiskais karogs", kurā tiek analizēta LU Karoga fonda nerealizēšanās 1990. gados, balstoties uz studentu/šu korporāciju vēstures avotiem LU Muzeja krājumā un līdzšinējiem pētījumiem. Tiek secināts, ka LU Karoga fonda nerealizēšanās cēlonis bija Latvijas studentu akadēmisko mūža organizāciju vēsturisko saikņu ar LU pārtrūkums sakarā ar aptuveni 50 gadus ilgušo PSRS okupāciju.
The article is a continuation of the Subject of the September 2021 "The Historical Flag of the University of Latvia", which analyses the failure of the University of Latvia Flag Foundation during 1990s, based on sources of student fraternity/sorority history in the collection of the Museum of the University of Latvia and previous research. It concludes that the reason for the non-realisation of the University of Latvia Flag Foundation was the severance of the historical links of Latvian student academical life organisations with the University of Latvia due to the occupation of the USSR for about 50 years.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Karogs; Studentu korporācijas; Studenti; Tradīcijas; Latvijas Universitāte; Flag; Student fraternities; Traditions; University of Latvia